2008
DOI: 10.1007/s10695-008-9204-7
|View full text |Cite
|
Sign up to set email alerts
|

Purification and characterization of α1-proteinase inhibitor and antithrombin III: major serpins of rainbow trout (Oncorhynchuss mykiss) and carp (Cyprinus carpio) blood plasma

Abstract: The main serine proteinase inhibitors of rainbow trout (Oncorhynchuss mykiss) and common carp (Cyprinus carpio) blood plasma were isolated and purified. The investigated inhibitors, alpha(1)-proteinase inhibitor (alpha(1)-PI) and antithrombin III (AT III), act by forming stable complexes with target proteinases. The association rate constants k (on) for the interaction of fish plasma inhibitors with several serine proteinases have been determined: k (on) for both carp and rainbow trout alpha(1)-PI were >10(7) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 35 publications
1
2
0
Order By: Relevance
“…Thus, the observation in the present study that r Aam S6, which has a neutral aa residue ‘Ser’ at the P1 site (Mulenga et al ., ), inhibited both trypsin and chymotrypsin is interesting though not unusual. Similar observations were reported for other serpins such as rainbow trout ( Oncorhynchuss mykiss ) and common carp ( Cyprinus carpio ) α1‐antiprotease inhibitor 1 (Mickowska, ) that also have polar neutral ‘Met’ at the P1 site. The apparent consistency of findings in the present study with other studies provides a measure of confidence in our data.…”
Section: Discussionsupporting
confidence: 82%
“…Thus, the observation in the present study that r Aam S6, which has a neutral aa residue ‘Ser’ at the P1 site (Mulenga et al ., ), inhibited both trypsin and chymotrypsin is interesting though not unusual. Similar observations were reported for other serpins such as rainbow trout ( Oncorhynchuss mykiss ) and common carp ( Cyprinus carpio ) α1‐antiprotease inhibitor 1 (Mickowska, ) that also have polar neutral ‘Met’ at the P1 site. The apparent consistency of findings in the present study with other studies provides a measure of confidence in our data.…”
Section: Discussionsupporting
confidence: 82%
“…Increased literatures reports that AAT-like proteins from seminal plasma, blood plasma, muscle, and serum of various fish exhibited similar biochemical characteristics [16][17][18][19]. Ayu AAT transcripts were present in a variety of tissues, with the highest level in the liver [12].…”
Section: Discussionmentioning
confidence: 98%
“…Although cDNA sequences encoding the ayu [12], carp [13], rainbow trout [14], and zebrafish [15] AATs have been documented, little reporting of the genomic structure of fish AAT can be found. Most studies have focused on the anti-proteinase characterizations of AAT, with few results shown on teleost immunological or anti-inflammatory functions [13,[16][17][18][19]. During the acute phase response, ayu AAT expression was significantly up-regulated at the mRNA and protein level [12], but expression in Atlantic cod [20] and rainbow trout [21] were found to be down-regulated.…”
Section: Introductionmentioning
confidence: 99%